Keberhasilan Manajemen Penjualan Zigzag Lasserwork Setvive di Semarang Menggunakan Java (Netbeans 7.3) - Harjunawati, Sri; Addin, Syahrial; Hendarsih, Ida; Marthanti, Amas Sari (Sistem Informasi Akuntansi Kampu Kabupaten Karawang, 2021)
This research examines the success of Sales Information System Management at Zigzag Lasser Work Service, Semarang, Indonesia. The proposed system is a computerized information system where data can be managed and integrated properly and built with Java programming (Netbeans 7.3) based on localhost. With the proposed Sales Information System, it is able to produce fast, accurate and timely information to facilitate processing of product data, order data, payment data, delivery data or delivery of goods. Sales reports and income reports are generated automatically with integrated processing so as to produce reports that are accurate, fast and can be justified. The speed of data processing and minimizing the occurrence of human error can help management reduce costs in order to apply economic principles to achieve maximum profit.